Hypokalemia and the Prevalence of Primary Aldosteronism - Gruber, Sven; Beuschlein, Felix (Hormone and Metabolic Research, 2020)
Hypokalemia is closely linked with the pathophysiology of primary aldosteronism (PA). Although hypokalemic PA is less common than the normokalemic course of the disease, hypokalemia is of particular importance for the manifestation and development of comorbidities. Specifically, a growing body of evidence demonstrates that hypokalemia in PA patients is associated with a more severe disease course regarding cardiovascular and metabolic morbidity and mortality. It is also well appreciated that low potassium levels per se can promote or exacerbate hypertension. The spectrum of hypokalemia-related symptoms ranges from asymptomatic courses to life-threatening conditions. Hypokalemia is found in 9–37% of all cases of PA with a predominance in patients with aldosterone producing adenoma. Conversely, hypokalemia resolves in almost 100% of cases after both, specific medical or surgical treatment of the disease. However, to date, high-level evidence about the prevalence of primary aldosteronism in a hypokalemic population is missing. Epidemiological data are expected from the recently launched IPAHK+study (“Incidence of Primary Aldosteronism in Patients with Hypokalemia”).
Keywords: primary aldosteronism; hypokalemia; potassium; hypertension